2018
DOI: 10.1039/c7dt04570k
|View full text |Cite
|
Sign up to set email alerts
|

Functional metal complexes from CuAAC “click” bidentate and tridentate pyridyl-1,2,3-triazole ligands

Abstract: Ligands containing the bidentate 2-pyridyl-1,2,3-triazole and tridentate 2,6-pyridyl-bis(1,2,3-triazole) moieties have emerged as alternatives to 2,2'-bypridine and 2,2':6',2''-terpyridine and other nitrogen-containing bi- and tri-dentate chelators. Because these "click" ligands are readily functionalised they are attractive options for the development of functional coordination complexes. This Frontiers Article discusses key recent reports on functional CuAAC "click" complexes in the areas of biological agenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Self-assembly studies have demonstrated that L2 coordinates with good affinity to zinc(II), copper(II), and palladium(II) ions, therebyf orm-ing metallomacrocycleso f1 :1 metal/ligand stoichiometry.B y taking advantage of different metal coordination geometries, the same organic ligand could be used to access severald ifferent topologies. Metallomacrocycles with square-planar copper(II) and palladium(II) ions were shown to act as stable exo receptors for small-molecule substrates, such as model-compound 4 and deoxyguanosine monophosphate (5). In the context of binding to more intricateb iological assemblies, [Pd II L2] exhibited promising stabilisation of guanineq uadruplexes with relativelyg ood quadruplex over duplexs electivity and offered some specificityt oward hybrida nd/orp arallel human telomeric G4 structures.H ere, increasedc onsideration of G4 binders with well-defined three-dimensional topologies may prove to be criticalf or the developmento fG 4b inders which are specific to individual G4 structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembly studies have demonstrated that L2 coordinates with good affinity to zinc(II), copper(II), and palladium(II) ions, therebyf orm-ing metallomacrocycleso f1 :1 metal/ligand stoichiometry.B y taking advantage of different metal coordination geometries, the same organic ligand could be used to access severald ifferent topologies. Metallomacrocycles with square-planar copper(II) and palladium(II) ions were shown to act as stable exo receptors for small-molecule substrates, such as model-compound 4 and deoxyguanosine monophosphate (5). In the context of binding to more intricateb iological assemblies, [Pd II L2] exhibited promising stabilisation of guanineq uadruplexes with relativelyg ood quadruplex over duplexs electivity and offered some specificityt oward hybrida nd/orp arallel human telomeric G4 structures.H ere, increasedc onsideration of G4 binders with well-defined three-dimensional topologies may prove to be criticalf or the developmento fG 4b inders which are specific to individual G4 structures.…”
Section: Resultsmentioning
confidence: 99%
“…Coordination-drivenself-assembly with the 2-(1,2,3-triazol-4-yl)pyridine motif The advent of "click" chemistry -amodulars trategy for the synthesis of new heterocycles [1] and other chemical functional groups -h as in recent years opened the doors to ah ost of novel ligands for transition-metal complexes of increasing complexity.I np articular, copper(I)-catalysed azide-alkyne cycloaddition (CuAAC) [2] has been extensively used due to the facile synthetic access it providest ot he 1,2,3-triazoleh eterocycle and its derivatives. [3] Of these derivatives,t he 2-(1,2,3-triazol-4-yl)pyridine chelate has attracted significant interestf or its unique binding, [3c, 4] optical, [5] magnetic, [4a, 6] and electrochemical [5b, 7] properties. In this chelate, coordination to the metal centre most commonly occurs through the pyridine as well as the triazoleN 3n itrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…1), we considered azobenzene 22 a promising choice of photochrome due to the relatively large change in its dipole moment upon trans-to-cis isomerization, 23 which could be associated with different solubilities. 24 Among the Pd ligands that are suitable for the Suzuki cross-coupling reaction, we turned to the click-derived pyridine-triazole structure, [25][26][27] due to its easy synthesis procedure and strong interaction with Pd to ensure homogeneous organometallic catalysis. 28,29 To test the hypothesis, we synthesized azobenzene derivatives 4 and 5 with incorporated pyridine-triazole ligands bearing a benzyl and a hexyl side chain, respectively (Scheme 1).…”
Section: Synthesis and Characterization Of Ligands And Pd Complexesmentioning
confidence: 99%
“…Cu(I)-catalyzed alkyne azide cycloadditon is the most classic method for synthesis of 1,4-disubstituted 1,2,3-triazoles. The structures of 1,2,3-triazoles and their assemblies are important for their diverse properties, especially for metalcoordination [11] and biological activity [8]. In continuation of our investigations on 1,2,3-triazole and related heterocycles chemistry [12], we synthesized the title compound (I) and obtained its crystal structure.…”
Section: Commentmentioning
confidence: 99%